Built and forgotten: unveiling the defects associated with the Ghana Cocoa Board (Cocobod) jubilee house in Kumasi - Agyekum, K.; Ayarkwa, J.; Amoah, P. (Penerbit Universiti Kebangsaan Malaysia, 2016)
Lack of attention given to government buildings in Ghana has resulted in the deplorable states of such buildings. This study sought to identify and examine key defects associated with the Ghana Cocoa Board (Cocobod) Regional Office building in Kumasi. A mixed research strategy which involved the use of on-site building observations and case studies was adopted. A checklist was prepared to assist in the identification of the defects, and the on-site building inspection assisted in examining the key defects identified. The findings from the study revealed that peeling of paints, leakages in ceilings, staining/discolouration of walls, dampness in walls and floors, electrical defects and cracked walls were among the key defects associated with the building. The on-site inspection carried out confirmed the severity of these defects, and revealed that the building was in a deplorable state. Though this study may not indicate the entire scenario of the deplorable states of many government buildings, it tries to explore some common defects affecting one of such buildings and the need to pay attention to them. The findings from this study provides the platform for all stakeholders involved to come together and fight the deteriorating states of government buildings in the country.